Dynamics of changes in total anthocyanins during the fermentative maceration of grapes - J. Balík (Horticultural Science, 2006)
This paper deals with the results of studies on changes in the content of total anthocyanins depending on their fermentative maceration from grapes of traditional Moravian cultivars (Blauer Portugieser, Saint Laurent and Blaufrankisch). Colouring matters were macerated in the course of alcoholic fermentation either in a closed rotary tank or in an open tank with a periodically plunging pulp cap. The losses resulting from adsorption of anthocyanins on yeast biomass were quantified. Concentration losses of anthocyanins were also observed in the course of fermentation of musts made of teinturier grape cultivars Alibernet and Neronet, when the skins of berries were separated. The process of fermentative maceration of anthocyanins from grape skins consisted of three dynamically different stages. In the stage with the exponential increase in the content of anthocyanins no significant differences were observed between the closed rotary tank technique and the open tank technique with periodic plunging of pulp cap. It was demonstrated that the losses of anthocyanins took place during the whole process of fermentation. The correlation between the anthocyanin losses and the production of yeast biomass was statistically highly significant.